Asking queer(er) questions: epistemological and methodological implications for qualitative inquirers. Issue 7 (9th August 2018) - O'Malley, Michael P.; Asher, Nina; Beck, Brandon L.; Capper, Colleen A.; Lugg, Catherine A.; Murphy, Jason P.; Whitlock, Reta Ugena
Abstract: This collection of distinct scholarly essays deliberatively turns to queer experience and theorizing as a resource for constructing vibrant qualitative research designs. Queer theory offers a breadth of epistemological and methodological possibilities for qualitative projects that are too frequently overlooked for many reasons. These reasons include frequently strict association of queer theory with queer research topics and researchers, as well as a concurrent reluctance to interrogate the representational needs of heterosexist culture served by the metaphor of the 'closet.' Queer theory also compels inquiry that takes up the unique circumstances of queer subjects. Locating educational inquiry within globally complex socio-historical dynamics and a post-Obergefell/post-2016 election U.S. context, this article poses multiple trajectories through which various scholars explore queer(er) qualitative inquiry in educational studies. These perspectives invite researchers to rethink qualitative inquiry designs through engagement with the queer, inclusive of research topics not initially perceived to be queer.